Numerical evaluation of the effect of air inlet and outlet cross-sections of a lithium-ion battery pack in an air-cooled thermal management system - Yu, Qibing; Abidi, Awatef; Mahmoud, Mustafa Z.; Malekshah, Emad Hasani; Aybar, Hikmet S. (Elsevier, 2022)
In this paper, airflow around 16 cylindrical lithium-ion cells placed in a square battery pack (BTP) is numerically examined. Laminar airflow enters the BTP from the top of the battery cells (BTC) and exits from the bottom of the BTP. In this three-dimensional analysis, the effect of the air inlet and outlet cross-sections on the temperature of the battery (T-BT) cells and the maximum and average T-BT pack is evaluated. The finite element method is used to solve the equations of battery and airflow. The results show that the upper part of the BTCs is at a lower temperature than the lower parts. The BTCs located in the middle of the BTP have a higher temperature than the ones located around the BTP. An increment in the air inlet cross-section reduces the average and the maximum T-BT pack. Enhancing the air outlet cross-section has little effect on the T-BT cells. The T-BT cells is enhanced until 1500 s, after which it is reduced because the airflow is diminished due to that the battery charging stops.
Keywords: Air-cooled; Inlet cross-section; Outlet cross-section; Thermal management